Taxonomic and biological notes on some Atlantic species of the snapping shrimp genus Synalpheus Spence Bate, 1888 (Decapoda, Alpheidae) - Anker, Arthur; Pachelle, Paulo P. G.; de Grave, Sammy; Hultgren, Kristin M. (Zootaxa, 2012)
The present study is a preliminary report on 36 Atlantic species of the snapping shrimp genus Synalpheus Spence Bate, 1888; 32 from the western Atlantic and four from the eastern Atlantic. The vast majority of specimens were collected along the Caribbean coast of Panama between 2005 and 2008 and around São Tomé Island in 2006. Additional specimens were collected in Costa Rica, Honduras, Belize, Mexico, Dominican Republic, Aruba, Venezuela, Florida, Brazil and Cape Verde, between 1998 and 2011. Some older museum material was also examined. Three nominal varieties or subspecies, viz. S. tumidomanus africanus Crosnier & Forest, 1965, S. tumidomanus congoensis Crosnier & Forest, 1965 and S. minus var. antillensis Coutière, 1909 are elevated to full species rank, becoming S. africanus, S. congoensis, and S. antillensis, respectively. Several species are reported for the first time from Panama, Honduras, Dominican Republic, Aruba, St. Martin, and Brazil. General taxonomic and/or ecological notes are provided for all species treated herein. The need for more taxonomic and molecular work is highlighted for the western Atlantic S. cf. africanus, S. anasimus Chace, 1972, S. apioceros Coutière, 1909, S. bousfieldi Chace, 1972, S. brooksi Coutière, 1909, S. fritzmuelleri Coutière, 1909, S. goodei Coutière, 1909, S. herricki Coutière, 1909, S. cf. longicarpus (Herrick, 1891), S. ul (Ríos & Duffy, 2007) and S. yano (Ríos & Duffy, 2007), as well as the eastern Atlantic S. cf. africanus. Most species reported are illustrated in colour, some for the first time. New sponge hosts are recorded for several species of the S. gambarelloides (Nardo, 1847) group. A table summarising life habits and social organisation for all presently known Atlantic species of Synalpheus is provided. Keys for the identification of all presently known western and eastern species of Synalpheus are also provided.